Perfume Consumers' Experiental Quality Has The Potential To Moderate The Role Of Planned Behavior On Revisit Intention - Ergo Nurpatria Kurniawan; Surya Bintarti; Sri Wahyuningsih; Ari Mulyono Hadi; Enur Hotimah (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2025)
This study aims to analyze the role of consumer behavior influenced by Subjective Norms, Attitudes and Behavioral Control on Revisit Intention, with Experiential Quality moderating on perfume products of Axe, Bellagio and Casablanca brands in Bekasi Regency. The perfume brands studied include Axe, Bellagio and Casablanca, which are included in this study is a quantitative type with a Non-Probability Sampling population using Purposive Sampling techniques to determine the respondents. Respondents who are part of the research population are consumers who use deodorant brands Axe, Bellagio and Casablanca. The data analysis technique used is regression analysis, with data processing using smartPls software. This study shows that subjective norms and consumer attitudes have a positive and significant effect on repurchase intentions, while behavioral control has no effect on revisit intentions. In addition, the moderating variable of experiential quality is able to strengthen the relationship between norms, attitudes, and revisit intention through consumers' positive experiences with the product.